Temperature Controls Onset and Period of NF-κB Oscillations and can Lead to Chaotic Dynamics - Heltberg, Mathias; von Borries, Mads; Bendix, Poul Martin; Oddershede, Lene B.; Jensen, Mogens H. (Frontiers in Cell and Developmental Biology, 2022)
The transcription factor NF-kB plays a vital role in the control of the immune system, and following stimulation with TNF-a its nuclear concentration shows oscillatory behaviour. How environmental factors, in particular temperature, can control the oscillations and thereby affect gene stimulation is still however an unsolved question. In this work, we reveal that the period of the oscillations decreases with increasing temperature. We investigate this using a mathematical model, and by applying results from statistical physics, we introduce temperature dependency to all rates, resulting in a remarkable correspondence between model and experiments. With the model we predict how this affects downstream protein production and find a crossover, where high affinity genes up-regulated at high temperatures. Finally we show oscillatory temperatures can entrain NF-kB oscillations and lead to chaotic dynamics presenting a simple path to chaotic conditions in cellular biology.